Perceptual quantification of active noise control in urban residential settings - Lim, Kelvin Chee Quan (Nanyang Technological University, 2022)
Noise exposure is an ironically neglected pollutant that is detrimental to public health, especially in dense urban cities. Although a proof-of-principle active noise control (ANC) system to mitigate environmental noise through open windows was recently developed in NTU, it is based on an energetic reduction of noise levels. Sound level alone often does not correlate with psychological quantities such as annoyance. This project seeks to quantify the perceptual effects of ANC on representative environmental noise types. The evaluation methodology is rooted in psychoacoustics and soundscape, wherein participants would be recruited to partake in a subjective experiment. The questionnaire to be presented to the participants would be developed on LabVIEW Web Module to interface with the ANC system. Student should be proficient with LabVIEW and possess a good understanding of basic acoustics concepts such as frequency weight, decibels, and sound pressure level.